The Effectiveness of A Safe Motorcycle Riding Behavior Promotion Program among High School Students in Mae Chai District, Phayao Province - Fongcham, Fasawang; Sirisopon, Nutthakritta; Phungdee, Theerapon (Journal of The Royal Thai Army Nurses, 2025)
A quasi-experimental study with two groups, measured before and after the experiment, was conducted to investigate the effectiveness of a safe motorcycle riding behavior promotion program among high school students in Mae Chai District, Phayao Province. The sample size was determined using the formula for calculating the sample size for comparing the means of two independent populations, resulting in a total of 56 participants. These participants were selected through simple random sampling and divided equally into an experimental group and a comparison group (28 students in each). The experimental group received the program for 4 weeks (one session per week, with each session lasting 45 minutes), while the comparison group received the regular curriculum and activities provided by the school. The research instruments included: The safe motorcycle riding behavior promotion program, and A questionnaire to evaluate the program. Data were analyzed using descriptive statistics (percentage, mean, standard deviation) and inferential statistics (Paired Samples t-test and Independent t-test). The results indicated that after participating in the program, the experimental group showed a significant increase in the average scores of safe motorcycle riding behavior compared to their pre-test scores, and their post-test scores were significantly higher than those of the comparison group at the .05 significance level. This demonstrated that the developed program could effectively promote safe motorcycle riding behavior among upper secondary school students.